Enforcement of stem-cell dormancy by nucleophosmin mutation is a critical determinant of unrestricted self-renewal during myeloid leukemogenesis - Maria Elena Boggio Merlo; Maria Mallardo; Lucilla Luzi; Giulia De Conti; Chiara Caprioli; Roman Hillje; Mario Faretta; Cecilia Restelli; Andrea Polazzi; Valentina Tabanelli; Angelica Calleri; Stefano Pileri; et al. (Haematologica)
Mutations in the NPM1 gene (NPMc+) and in the FLT3 gene (FLT3-ITD) represent the most frequent co-occurring mutations in Acute Myeloid Leukemia (AML), yet the cellular and molecular mechanisms of their cooperation remain largely unexplored. Using mouse models that faithfully recapitulate human AML, we investigated the impact of these oncogenes on pre-leukemic and leukemic hematopoietic stem cells (HSCs), both separately and in combination. While both NPMc+ and Flt3-ITD promote the proliferation of pre-leukemia HSCs, only NPMc+ drives extended selfrenewal by preventing the depletion of the quiescent HSC pool. Quiescent HSCs exist in a dynamic equilibrium between dormant and active states, which respectively support self-renewal and regenerative haematopoiesis. Transcriptional profiling of these dormant and active states revealed that not only does NPMc+ stimulate the transition from dormancy to activity but it also reinforces the dormant state, thereby ensuring the replenishment of dormant HSCs. Intriguingly, the coexpression of NPMc+ and Flt3-ITD engenders a novel phenotypic state within quiescent HSCs, whereby dormancy and activity co-exist within a single cell. We posit that this unique state fuels the in vivo expansion of self-renewing HSCs and facilitates the rapid selection of leukemiainitiating cells. Pharmacological inhibition of the dormancy-related TGFβ1 - pathway effectively reduces the self-renewal capacity of leukemia SCs and extends survival in our mouse models. Collectively, these findings demonstrate that enforcement of HSC dormancy is a critical determinant of unrestricted self-renewal during leukemogenesis and, as such, represents a compelling target for the development of novel anti-leukemic therapies.